The Degree of Jordanian Secondary School Principals' Practice of Visual Management from the Teachers' Point of View - Omar Aiasreh; Saleh Ababneh (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
This study aims to identify the degree to which the principals of public secondary schools in Jordan practice visual management from the teachers' point of view. To achieve the objectives of the study, a descriptive survey method was used. For this purpose, a questionnaire consisting of (49) items was developed and divided into three areas: work rules, diagnosis, and eliminating waste. After verifying the validity and reliability of the questionnaire, it was distributed to a random sample of (375) individuals in the second semester of the academic year (2019-2020). The results of the study showed that the degree of school principals' practice of visual management from the teachers' point of view was moderate. The results also showed the presence of statistically significant differences in the degree of school principals' practice of visual management due to gender in favor of females, and to experience in favor of those with experience of ten years or more. Based on the findings, the researcher recommends that the Ministry of Education in Jordan hold training courses for school principals in order to familiarize them with the issue of visual management to be applied in their schools because of its great importance in developing school administration.